Hematopoietic Stem Cell Transplantation in Primary Immunodeficiency Diseases: Current Status and Future Perspectives - Castagnoli, Riccardo; Delmonte, Ottavia Maria; Calzoni, Enrica; Notarangelo, Luigi Daniele (Frontiers in pediatrics, 2019)
Primary immunodeficiencies (PID) are disorders that for the most part result from mutations in genes involved in immune host defense and immunoregulation. These conditions are characterized by various combinations of recurrent infections, autoimmunity, lymphoproliferation, inflammatory manifestations, atopy, and malignancy. Most PID are due to genetic defects that are intrinsic to hematopoietic cells. Therefore, replacement of mutant cells by healthy donor hematopoietic stem cells (HSC) represents a rational therapeutic approach. Full or partial ablation of the recipient's marrow with chemotherapy is often used to allow stable engraftment of donor-derived HSCs, and serotherapy may be added to the conditioning regimen to reduce the risks of graft rejection and graft versus host disease (GVHD). Initially, hematopoietic stem cell transplantation (HSCT) was attempted in patients with severe combined immunodeficiency (SCID) as the only available curative treatment. It was a challenging procedure, associated with elevated rates of morbidity and mortality. Overtime, outcome of HSCT for PID has significantly improved due to availability of high-resolution HLA typing, increased use of alternative donors and new stem cell sources, development of less toxic, reduced-intensity conditioning (RIC) regimens, and cellular engineering techniques for graft manipulation. Early identification of infants affected by SCID, prior to infectious complication, through newborn screening (NBS) programs and prompt genetic diagnosis with Next Generation Sequencing (NGS) techniques, have also ameliorated the outcome of HSCT. In addition, HSCT has been applied to treat a broader range of PID, including disorders of immune dysregulation. Yet, the broad spectrum of clinical and immunological phenotypes associated with PID makes it difficult to define a universal transplant regimen. As such, integration of knowledge between immunologists and transplant specialists is necessary for the development of innovative transplant protocols and to monitor their results during follow-up. Despite the improved outcome observed after HSCT, patients with severe forms of PID still face significant challenges of short and long-term transplant-related complications. To address this issue, novel HSCT strategies are being implemented aiming to improve both survival and long-term quality of life. This article will discuss the current status and latest developments in HSCT for PID, and present data regarding approach and outcome of HSCT in recently described PID, including disorders associated with immune dysregulation.